Molecular diversity analysis of planctomycete like bacteria in inosine fermentation and municipal wastewater treatment systems - Hao Zhang; Ying Xu; Yifeng Ding; Qingxiang Yang; Siwei Ren; Xueling Li; Xuanyu Chen; Yuanyuan Xu; Hongxin Hao (African Journal of Environmental Economics and Management, 2021)
In this study, the diversity of planctomycete-like bacteria in an inosine fermentation and a municipal wastewater treatment plants was investigated by denaturing gradient gel electrophoresis (DGGE) of nested polymerase chain reaction (nested PCR) amplified 16S rRNA gene fragments using planctomycete-specific forward primer and a bacteria universal reverse primer. The bacterial community structures in the two wastewater treatment systems were obviously different due to the different treatment processes and different wastewater characteristics. The highest similarity of the microbial community structure happened in the two samples from the acidification and the anaerobic tank in inosine fermentation plant reaching 67%. While the two samples from the anaerobic and the aerobic tank of municipal wastewater treatment plant reached 66%. Ten sequences were recovered from the DGGE gel and were assigned to Clostridia, Proteobacteria, Bacteroidete and Candidate division based on the phylogenetic analysis. The two sequences grouped into Candidate division had more than 92% similarities with the Planctomycete-like bacterial clones. However, no anaerobic ammonium oxidation (anammox) activities were detected in the samples of these two wastewater treatment plants.